(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
Human rights are considered a guarantee for all individuals to obtain a good standard of living characterized by justice and equality. They are the primary support for human development and benefiting from the skills and abilities he has. Human rights also provide protection for individuals from those who possess power or power and use it to harm others or prevent them from living in dignity. And not enjoying their freedoms. The research presents the most important concepts related to human rights, their importance and characteristics. It also reviews international bodies and organizations working in the field of human rights and their most important activities. The importance of the research lies in that it gives a comprehensive and summarized idea of ​​this important topic that has become the concern of all countries and activists at all levels in international and local communities.